Work issues for persons recovering from psychiatric conditions - Pang, Si Hui (2017)
The current study seeks to qualitatively assess and understand how “Persons in Recovery” (PIRs; or individuals recovering from psychiatric conditions) construe work, the issues they face, and the facilitating factors to sustained and meaningful employment. Eight participants, aged 25 to 49, took part in semi-structured interviews designed to elicit their narratives and perspectives on work. Data was analysed using directed content analysis. All participants affirmed the significance of work, but also faced individual, workplace, and social challenges. Among the issues faced, participants highlighted the importance of self-management, and their loss in confidence and self-efficacy. Participants also described experiences of stigma, which lead to fears of disclosure in the workplace. These challenges were exacerbated by a competitive job market and an uncertain economy. Social support and formal support from service providers were deemed instrumental to vocational success. However, as service-users, participants highlighted the need for greater transparency and partnership in their care plans. In view of the findings, the Enabling Employment Initiative is proposed. This initiative seeks to create an inclusive society through targeting the public, employers, and service providers, as well as simultaneously empowering PiRs to participate in the labour market. The overarching aim of this initiative is to create an enabling environment where PiRs can fully participate as valued members of society.